PENGARUH PENDAPATAN TERHADAP KONSUMSI DAGING DAN TELUR DI KECAMATAN SIAU BARAT KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Badoa, Irgin V; Salendu, A H.S; Elly, F. H; Waleleng, P O.V (Universitas Sam Ratulangi, 2016)
ABSTRACT EFFECT OF INCOME ON MEAT AND EGG CONSUMPTION IN WEST SIAU DISTRICT OF THE SIAU TAGULANDANG BIARO REGENCY. Generally, coastal farmer community have low income causing consumptions of livestock product are low. West Siau district was including in the Siau Tagulandang Biaro Island regency as the coastal area. Majority of the population of this regency were household farmer and fisher men, causing consumption of livestock product depended on their income. Objective of this study was to evaluate the effect of income on meat and egg consumption in West Siau district. Samples of villages were defined using purposive sampling method, referring to villages with high population staying on the coastal area including villages of Pelingsawang, Peling and Paniki. Data were collected using survey method including primary and secondary data. Household farmers were defined based on simple random sampling with the total of 41 persons. Variables observed were total meat consumption, total egg consumption and income per capita. Data were analyzed by simple regression analysis. Results showed that total income of household farmer were IDR 136,660,000 with the average of IDR 3,333,171 per household farmer per month. Total chicken meat, pork and egg consumptions were 58.5 kg, 27.5 kg and 17.4 kg per month, respectively. Average investment to consume meat and eggs were IDR 122,195 or 3.67 percents of the family income. Average meat consumption at West Siau district were 7.72 kg per capita per year, consisted of chicken meat and pork of 4.84 kg and 2.88 kg per capita per year, respectively. Average of egg consumption were 1.49 kg per capita per year. Therefore, income of the family significantly affected meat and egg consumption in West Siau district of the Siau Tagulandang Biaro regency. Keywords: Income, meat and egg consumption, Siau district.